The LCNetWork: An electronic representation of the mRNA-lncRNA-miRNA regulatory network underlying mechanisms of non-small cell lung cancer in humans, and its explorative analysis. (December 2022) - Chaturvedi, Aparna; Som, Anup
Abstract: Advancement in genomics technologies have made it possible to identify the genes and their interaction/regulation involved in NSCLC, but the interaction information are scattered over the literature. Thus, there is a need of assembling all the available interaction/regulation information in a single platform which will provide a complete view of NSCLC mechanisms. Further, analysis of the mechanisms underlying NSCLC in humans would benefit substantially from easy access to an electronic network. We, therefore, used manual literature curation and integrated all the existing knowledge of NSCLC biomarkers (mRNA, lncRNA and miRNA) into a single conceptual platform represented through a biological network, termed the LCNetWork which represents 345 genes (195 mRNA, 46 lncRNA and 104 miRNA) and 500 direct interactions that are crucial to the regulation of NSCLC in humans. Furthermore, through exploratory data analysis, we have reported four mRNAs (PLK1, ZNF300, NKX2–1, and EGR1), one lncRNA (UCA1) and five miRNAs (MIR133B, MIR326, MIR429, MIR451A, and MIR944) and MIR193A/UCA1/EGFR axis crucial to NSCLC mechanisms. The GO results suggested their role in post-transcriptional gene silencing and RNA polymerase II activities as causes leading to cancer metastasis. The LCNetWork provides up-to-date knowledge of the genes and their interaction/regulation information in NSCLC and is capable of revealing multiple cancer-gene landscapes. Additionally, the LCNetWork has been provided in the Network Data Exchange portal as an electronic circuit for growth by community-level effort. Graphical Abstract: ga1 Highlights: Integrated all the experimentally reported knowledge on the NSCLC mechanisms into a single conceptual platform. Assembled an mRNA-lncRNA-miRNA regulatory network underlying molecular mechanisms of NSCLC. Identified four mRNAs, five miRNAs, one lncRNA, and MIR193A-UCA1-EGFR axis crucial to NSCLC regulation. Suggested post-transcriptional gene silencing and RNA polymerase II activity as major factors leading to NSCLC progression. The LCNetWork has been made publicly available for community use and contribution.